2016
DOI: 10.1016/j.joep.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rewards on tax compliance decisions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This study refers to tax fairness as the distribution of sales tax registration threshold and sales tax penalties in a fair manner by the tax authority, with fair cost falling on the registered sales tax. A positive relationship was established between tax fairness and tax compliance behavior by some prior studies (e.g., Fochmann & Kroll, 2015;McKerchar, Bloomquist, & Pope, 2013;Kirchler & Wahl, 2010;Feld & Frey, 2007), others reported no relationship (e.g., Benk, Ç akmak & Budak, 2011), while some others like Sinnasamy, Bidin and Syed-Ismail (2015) reported mixed results. In the sales tax context, literature also showed a positive tax fairness-sales tax compliance association (Woodward & Tan, 2015;Adams & Webley, 2001).…”
Section: Determinants Of Sales Tax Compliancementioning
confidence: 90%
“…This study refers to tax fairness as the distribution of sales tax registration threshold and sales tax penalties in a fair manner by the tax authority, with fair cost falling on the registered sales tax. A positive relationship was established between tax fairness and tax compliance behavior by some prior studies (e.g., Fochmann & Kroll, 2015;McKerchar, Bloomquist, & Pope, 2013;Kirchler & Wahl, 2010;Feld & Frey, 2007), others reported no relationship (e.g., Benk, Ç akmak & Budak, 2011), while some others like Sinnasamy, Bidin and Syed-Ismail (2015) reported mixed results. In the sales tax context, literature also showed a positive tax fairness-sales tax compliance association (Woodward & Tan, 2015;Adams & Webley, 2001).…”
Section: Determinants Of Sales Tax Compliancementioning
confidence: 90%
“…Some studies have confirmed the positive impact of the pertinent information and messageframing on tax compliance (Fochmann & Kroll, 2016;Gangl et al, 2016;Hofmann et al, 2008;Sussman & Olivola, 2011). Moreover, it has also been found that more significant effect can be reached if the message is correctly directed according to taxpayers´ promotion and prevention focus (Holler et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 84%
“…In the present work, tax fairness is defined as the distribution of sales tax registration threshold and sales tax penalties in all fairness by the tax authority entity, with fair cost manifested in registered sales tax. For this construct, Fochmann and Kroll (2015), McKerchar et al (2013), Kirchler and Wah (2010) and Feld and Frey (2007) reported a positive tax fairness-tax compliance behavior relationship, Benk et al (2011) reported the lack of a significant relationship, whereas Saymeh and Sabha (2015) reported a combination of findings. However, in the sales tax context, Woodward and Tan (2015) and Adams and Webley (2001) supported a positive relationship between the two variables.…”
Section: Literature Reviewmentioning
confidence: 99%